1999
DOI: 10.1023/a:1006297225577
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In a three-year study, mite populations were monitored in two vineyards, each having two grape varieties with different leaf hair density. In both vineyards native phytoseiids were present: Amblyseius andersoni in one vineyard, and Phytoseius finitimus in the other. The economically important predators Kampimodromus aberrans and Typhlodromus pyri were released in both vineyards in order to study their efficacy in controlling tetranychids and eriophyids and their persistence during periods of prey scarcity. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
13
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 1 publication
5
13
1
Order By: Relevance
“…As one example, Seelmann et al (2007) showed that the smaller Kampimodromus aberrans (Oudemans) is less vulnerable to IGP from the larger phytoseiid Euseius Wnlandicus Oudemans on pubescent leaves while the reverse is true for E. Wnlandicus. Observations in vineyard systems in Italy are consistent with these results where the larger Amblyseius andersoni (Chant) is more likely to become established in more glabrous varieties while the smaller T. pyri becomes established in more pubescent varieties (Camporese andDuso 1996, Duso andVettorazzo 1999).…”
supporting
confidence: 70%
“…As one example, Seelmann et al (2007) showed that the smaller Kampimodromus aberrans (Oudemans) is less vulnerable to IGP from the larger phytoseiid Euseius Wnlandicus Oudemans on pubescent leaves while the reverse is true for E. Wnlandicus. Observations in vineyard systems in Italy are consistent with these results where the larger Amblyseius andersoni (Chant) is more likely to become established in more glabrous varieties while the smaller T. pyri becomes established in more pubescent varieties (Camporese andDuso 1996, Duso andVettorazzo 1999).…”
supporting
confidence: 70%
“…However, a few studies focused on the relationship between predatory mites and the pollen of the plants on which these predators occur. Such a relationship was suggested for citrus (Kennett et al, 1979;Grout and Richards, 1992), avocado (McMurtry and Johnson, 1965;Maoz et al, 2008;Gonzalez-Fernandez et al, 2009) and grapevine (Duso and Vettorazzo, 1999). Daud (2003) studied the effect of pollen of Mabea fistulifera Mart.…”
Section: Plants As Reservoir Zones For Predatory Mitesmentioning
confidence: 95%
“…This can be achieved by increasing habitat complexity/diversity to provide refuges and alternative hosts and food resources to predators and parasitoids (Costello and Daane 2003;Duso et al 2004;Ponti et al 2005;Zanolli and Pavan 2011;Pozzebon et al 2015a;Wilson et al 2015) and reducing the use of non-selective pesticides (e.g., Jepsen et al 2007, Pozzebon et al 2015b. Biological control strategies against sucking pests can also be enhanced by inoculative or augmentative releases of natural enemies (Duso et al 1985;Daane et al 1996;Duso and Vettorazzo 1999;Daane et al 2008). Irrigation, fertilization, and cultivar choice can be also managed to reduce pest incidence and economic damage (Daane and Williams 2003;Costello 2008;Fornasiero et al 2012Fornasiero et al , 2016Cocco et al 2015).…”
Section: Ecological Engineering For Pest Suppression: Habitat Manipulmentioning
confidence: 99%